2015
DOI: 10.3899/jrheum.141385
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3η Autoantibodies: Diagnostic Use in Early Rheumatoid Arthritis

Abstract: 14-3-3η autoantibodies, alone and in combination with the 14-3-3η protein, RF, and/or ACPA identified most patients with early RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 20 publications
1
21
3
1
Order By: Relevance
“…The prevalence of 14-3-3η positivity in children with PJIA RF + was similar to that in another study on early undifferentiated polyarthritis in adults. However, in both early and established RA, a higher prevalence of 14-3-3η (68%) was reported compared to our pediatric population [17,18]. In a previous report, 14-3-3η was positive in 21% of patients with early RA who were seronegative for RF and CCP antibodies, and in 67% of patients with seronegative established RA and in a pediatric study, 31% of PJIA RF-patients had positive 14-3-3η levels [15,19].…”
Section: Discussioncontrasting
confidence: 63%
“…The prevalence of 14-3-3η positivity in children with PJIA RF + was similar to that in another study on early undifferentiated polyarthritis in adults. However, in both early and established RA, a higher prevalence of 14-3-3η (68%) was reported compared to our pediatric population [17,18]. In a previous report, 14-3-3η was positive in 21% of patients with early RA who were seronegative for RF and CCP antibodies, and in 67% of patients with seronegative established RA and in a pediatric study, 31% of PJIA RF-patients had positive 14-3-3η levels [15,19].…”
Section: Discussioncontrasting
confidence: 63%
“…Patients with colon, ovarian, breast and lung cancer as well as patients with SLE have been found to produce autoantibodies against the c-Myb protein (40). Both categories of patients generate autoantibodies against cyclin-B1, survivin, p16, 14-3-3 proteins, eukaryotic translation initiation factor 4G (eIF-4G) and RAF1 (14,27,28,(34)(35)(36)(40)(41)(42)(43)(44)(45)(46)(47)(48). Autoantibodies against the cyclic citrullinated peptide (CCP) were detected in patients with Sjogren's syndrome and psoriatic arthritis (51, 52) as well as in lymphoma patients (49).…”
Section: Immune Response To Self Antigens In Cancer Patients Partly Cmentioning
confidence: 99%
“…However, early RA especially serum RF and anti-CCP antibody-negative is di cult to diagnose due to the lack of effective biomarkers. Although studies have reported that some biomarkers, such as 14-3-3η autoantibodies and calprotectin, may be effective in the diagnosis of early RA, they have not been used in its clinical diagnosis [4][5][6][7]. Therefore, it is vital to identify new and effective biomarkers for the early diagnosis and treatment of RA.…”
Section: Introductionmentioning
confidence: 99%